Swedish Experiences From 60 Years of Screening and Breeding Programs for Hip Dysplasia—Research, Success, and Challenges - Hedhammar, Åke (Frontiers in Veterinary Science, 2020)
A screening program for hip dysplasia (HD) was introduced in Sweden during the 1950s for German shepherd dogs, before for a few breeds and now any breed. Degree of canine HD was originally graded 1–4 (slight, mild, moderate, and severe) and used in Swedish screening program up to year 2000 and was thereafter replaced by letters A–E with A and B for no signs/near normal, C for mild, D for moderate, and E for severe HD. Final scoring is based on “the worst” side. In Sweden, 70% of all dogs are registered by the Swedish Kennel Club, and in relevant breeds, almost all breeding stock and 30–50% of all dogs are screened for HD. By an extensive database of all dogs registered since 1976 and mandatory identification by microchip, all results can be linked to dogs well-defined by identity and ancestral background. An implementation of structured screening and genetic health programs resulted in markedly decreased prevalence of HD already during the 1980s. The programs are based on open registries and on positive as well as negative results for identified individuals linked to their ancestral background. The successful decrease in moderate and severe HDs is illustrated for seven common breeds. However, there is also the challenge of a further decrease when already almost all breeding is performed with unaffected breeding stock. Handling that and the increased relative prevalence of less severe grades of HD (grade C) calls for breed-specific breeding strategies, taking into account the prevalence and clinical significance in each breed. Further decrease might rather be achieved by using estimated breeding values and genomic selection instead of more extensive and costly screening procedures. For the public perception of HD, the value of a clear distinction between grades D and E as a good predictor of the clinical entity vs. grade C as a tool to refine the selection criteria for breeding stock is indicated.